A Systematic Review of Indonesian Veterinary Research on Abattoir and Animal Slaughtering: Scientific Methods and Approaches - Handoko, Jully; Suryadi, Untung; Siregar, Ariyawan; Andryan, Azriel Vigo; Fahrizi, Dio; Asror, Maulana Abil (Universitas Airlangga, 2025)
Background: Veterinary research on abattoirs and animal slaughter published in Indonesian journals requires comprehensive evaluation due to its close relevance to animal-derived food production and public health. Purpose: This systematic review analyzes studies on abattoirs and slaughter practices published from 2014 to 2024 in 20 Indonesian veterinary journals, including 13 SINTA-accredited and 7 non-accredited journals. Review: A total of 37 articles were examined to identify research themes, methodological approaches, study designs, analytical techniques, and disciplinary focuses. Result: Publication trends over the decade fluctuated, with no significant correlation between publication year and article count (r = 0.43; p > 0.05). Cattle were the most frequently examined species (13 studies), showing a significant difference in the distribution of research subjects (χ² = 79.50; p = 6.15 × 10-14). Quantitative and mixed-method approaches were the most commonly used (17 and 19 studies), and their adoption differed significantly (χ² = 11.80; p = 0.0027). The descriptive survey design dominated the literature (32 studies), with a significant difference from other designs (χ² = 21.85; p = 0.000018). Differences in analytical techniques were not significant (χ² = 94.49; p = 1.47 × 10-19), although descriptive analysis was most frequently applied. Veterinary public health was the primary disciplinary focus (15 studies), but the overall disciplinary distribution was not significantly different (χ² = 1.121; p = 0.993). Conclusion: This review provides a concise overview of research priorities and methodological patterns in Indonesian veterinary literature on abattoirs and animal slaughter. The findings highlight the dominance of descriptive and mixed-method studies, the strong focus on public health, and the need for more diverse methodological and disciplinary approaches in future research.